The Roots of Criticism.Heterodox Notes for a Reading of the Critical Work of Jaime Mejía Duque (1933-2009) (2017)
The critical work of Jaime Mejía Duque (1933 - 2009) has never been read in a comprehensive way, reconstructing his theoretical positions and evaluating their relevance to the field of Colombian and Latin American literary criticism. The goal of this paper is to explain one of his three critical coordinates, which I have called “psychology of poetic creation: ontogenesis of literary talent”. The remainingcoor - dinates are his philosophy of history and his interpretation of different kinds of realism; briefly described in the text.